The Influence of Korean Pop Culture on the Narrative Structure of Indonesian Fanfiction on Wattpad - Putra, Deva; Saefullah, Rifki (International Journal of Humanities, Law, and Politics, 2025)
The Korean Wave or Hallyu phenomenon has had a significant influence on global popular culture, including in Indonesia. One form of this influence is seen in the production of fanfiction on digital platforms such as Wattpad. This study aims to analyze the influence of Korean culture on the narrative structure and intertextuality practices in Indonesian-language fanfiction with a Korean theme. The approach used is qualitative-descriptive analytical with Tzvetan Todorov's narrative theory and the concept of intertextuality as the basis for analysis. The objects of the study consisted of five popular fanfictions on Wattpad that carried the themes of K-pop and K-drama. The results of the analysis show that the narrative structure of the five fanfictions follows the classic pattern of Korean drama, which consists of the stages of equilibrium, disturbance, conflict, resolution, and achieving a new balance. Elements of intertextuality emerge through the use of character names, setting, emotional conflict, and language styles that resemble Korean drama dialogues. Indonesian fanfiction writers not only imitate, but also creatively adapt elements of Korean culture, combining them with local social and cultural contexts. From the readers' perspective, there is high enthusiasm for narratives that are full of Korean elements, indicating a horizon of hope formed from the consumption of global popular culture. In conclusion, Korean-themed fanfiction on Wattpad becomes a dialogical space between global culture and local expression, while also reflecting forms of creative literacy and cultural hybridization in the digital era.